Evaluation The Correlation Between Age, Gender, And The Incidence Of Cervical Lesions - Ainil Husna Amin; Muhammad Hafiz Yaakob; Wan Zulfadli W. M. Nasir; Aws H. Ali Al-Kadhim (Asclepius Open Medical Journals, 2024)
Clinical Research In Dentistry • Vol 1 • Issue 1 • 2018